RELIGIOUS TRANSFORMATION IN EARLY ENGLISH LITERATURE: FROM PAGAN MYTHS TO CHRISTIAN SYMBOLISM - Kuatbaeva Sayatxan Maxmudovna,Scientific adviser: Khamitov Eldorbek E. (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
This study examines the religious transformation in early English literature, focusing on the shift from pagan myths to Christian symbolism. Texts such as Beowulf and The Dream of the Rood reflect a cultural transition in which traditional pagan beliefs coexist with emerging Christian ideology. Pagan motifs heroic valor, fate, and mythic creatures are often reinterpreted within a Christian framework, emphasizing moral lessons, divine providence, and spiritual redemption. Early English poets integrated older mythic elements with Christian themes, creating layered narratives that address both earthly and spiritual concerns. This synthesis illustrates how literature functioned as a medium for negotiating cultural and moral values during the Anglo-Saxon period. Understanding this transformation provides insight into the ethical, spiritual, and literary dynamics of early English society.